Self-management in adults after solid-organ transplantation: a scoping review protocol. Issue 1 (24th January 2023) - Jobst, Stefan; Stadelmaier, Julia; Zöller, Petra; Grummich, Kathrin; Schmucker, Christine; Wünsch, Alexander; Kugler, Christiane; Rebafka, Anne
Abstract : Introduction: After solid-organ transplantation (SOTx), recipients must adhere to a lifelong medical regimen, change their lifestyle and cope with physiological and psychosocial challenges. This requires active participation in their care and self-management abilities. The concept of self-management after SOTx has only been described regarding specific organs and focused on adherence to medical treatment. A comprehensive conceptualisation of self-management entailing all solid organs and beyond medical aspects does not exist. This might lead to unmet self-management support needs of SOTx recipients and hinder a more holistic and integrative approach in self-management support. Therefore, a better understanding of the concept of self-management after SOTx is needed to facilitate a comprehensive evidence base for healthcare providers and researchers. The purpose of this scoping review is to explore existing evidence on self-management in adults after SOTx. Methods and analysis: To identify relevant evidence, six electronic databases and three study registers will be searched, supplemented by handsearches, reference checking and expert recommendations. Screening and selection of available evidence will be carried out in a two-step process by two independent reviewers. International evidence published in English or German reporting on adults after heart, lung, liver, pancreas, kidney or small bowel transplantation will be considered. To meet inclusion criteria, articles have to focus on either: self-management, self-management support or recipients' or healthcare providers' perspectives of challenges and needs potentially addressable by self-management. Data extraction will be performed by two reviewers independently using a structured form. Data will be analysed descriptively and using content analysis procedures. Findings will be summarised narratively and presented in tabular format. Ethics and dissemination: The consultation and approval of an ethics committee is not required for this scoping review. Findings of the scoping review will be published in a peer-reviewed open-access journal and presented at conferences.